Medication adherence self-report instruments: Implications for Practice and Research - Rolley, John; Davidson, Patricia; Dennison, C.; Ong, A.; Everett, B.; Salamonson, Y. (Lippincott Williams and Wilkins, 2008)
After an acute cardiac event, adhering to recommendations for pharmacologic therapy is important in achieving optimal health outcomes. Considering the impressive evidence base for cardiovascular pharmacotherapy, strategies for promoting adherence in the research and clinical settings is challenging. The aim of this article was to review published self-report measures assessing and monitoring medication adherence in cardiovascular disease and provide recommendations for reserach into medication adherence.Despite the problems with medication adherence identified in the literature, only 7 instruments met the search criteria. There was limited use of instruments across studies and setting to enable comparison across populations and extensive psychometic evaluation. Medication adherence is a complex, multifaceted construct dependent on a range of physical, social, economic, and psychological considerations. In spite of the importance of adherence in ensuring optimal cardiovascular outcomes, conceptual underpinnings and methods of assessing medication adherence require further discussion and debate.